MAGNETIC SUSCEPTIBILITY AS INDICATOR OF VEHICLE POLLUTION OF THE TOPSOIL IN ODESA CITY - Stakhiv, I.; Tsiupa, I.; Bondar, K.; Korol, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The work is devoted to proving the use of low-frequency mass-specific magnetic susceptibility (χ) as an indicator of geochemical soil pollution from mobile sources in Odesa. The main task was to find the correlation between the soil χ and the content of heavy metals that are present in the emissions of vehicles. On 98 soil samples of magnetic susceptibility, the frequency dependence of magnetic susceptibility (kfd) was measured on Bartington MS 2B Dual Frequency Sensor. The bulk content of Cu, Mn, Ni, Pb, Zn, Cd was determined from atomic absorption spectrometry. The χlf varies from 44 to 624*10–8 m3/kg with a median value 146.9*10–8 m3/kg. Bulk content of Pb, Cu, Zn in soils of Odesa demonstrate substantial increase on background level. The significant linear correlations are observed both between χ and contents of Cu, Zn and Pb and between elements of this geochemical association. The maps of χ and PLI (pollution load index) were calculated by Pb, Cu, Zn. They show that high values related to automobile roads and railways. Anthropogenic magnetic iron compounds and heavy metals in soils of Odesa are accumulated mainly from vehicle emissions. Originality of the study is in using magnetic properties of soils to delineate contaminated areas in Odesa city. Magnetic monitoring can be recommended to control the anthropogenic pollution in Odessa, in particular for the assessment of vehicle emissions contribution.